2019
DOI: 10.1002/ccr3.2304
|View full text |Cite
|
Sign up to set email alerts
|

Successful cryoballoon ablation of a focal atrial tachycardia in a patient with situs inversus and dextrocardia

Abstract: Cryoballoon ablation of an arrhythmogenic focus alongside a pulmonary vein as an alternative to radiofrequency ablation may be feasible and safe in patients with situs inversus and dextrocardia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
0
0
Order By: Relevance
“…In recent years, in addition to radiofrequency ablation, balloon cryoablation has also been used to treat arrhythmias in patients with dextrocardia. Akkaya et al 16 reported the first case of cryoballoon ablation in a patient with focal atrial tachycardia in dextrocardia. The successful ablation of abnormal potentials originating in the superior pulmonary vein inferior to the ramus under the guidance of the Ensite system suggests that cryoballoon ablation may also be safe and feasible in patients with dextrocardia combined with arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, in addition to radiofrequency ablation, balloon cryoablation has also been used to treat arrhythmias in patients with dextrocardia. Akkaya et al 16 reported the first case of cryoballoon ablation in a patient with focal atrial tachycardia in dextrocardia. The successful ablation of abnormal potentials originating in the superior pulmonary vein inferior to the ramus under the guidance of the Ensite system suggests that cryoballoon ablation may also be safe and feasible in patients with dextrocardia combined with arrhythmias.…”
Section: Discussionmentioning
confidence: 99%